WHEN THE EARTH CONQUERS THE HEAVEN: A STUDY OF NARRATOLOGY ON KANA INAI ABANG NGUAK IN THE PERSPECTIVE OF A. J. GREIMAS - Astuti, Sri; Taum, Yoseph Yapi (International Journal of Humanity Studies (IJHS), 2017)
Kana Inai Abang Nguak is a folk lyric by the society of Dayak Desa which is spoken in formal ritual language by chanting. The characters in kana are usually related with the life in nirvana and represents the thoughts and world view of Dayak society. This paper is meant to discuss one kana entitled Inai Abang Nguak using narratology perspective of A. J. Greimas. Greimass narratology studies gradually reveal surface structure and deep structure of a story. Surface structure reveals the context and story sequences. Deep structure reveals the syntax structure (actantial and functional scheme) and also semantic structure, which are three semantic axis including desire pursued axis, power axis, and communication axis. The text Inai Abang Nguak consists of seven-sequence(act)-story actantial scheme which centers on Inai Abang as the subject of the story. The success of earth in conquering the heaven (nirvana) is caused by three factors: 1) although the heaven is blessed with eternal life, the heaven is actually blood-related with this earth; 2) the heavens act in capturing earths ritual leaders is a heavy violation that has to be fought against by the earth; 3) the power of the earth as one unit (human beings, animals, spirits, and magical powers) to attack the heaven and bring back harmony to the earth. It can be concluded that Greimas narratology can be used to understand surface structure, deep structure, and even discursive structure of a folk story.